PROTECTIVE EFFICACY OF TRIDAX PROCUMBENS AND FICUS RELIGIOSA AGAINST ISONIAZID AND RIFAMPICIN INDUCED HEPATOCELLULAR DAMAGE IN RATS: A PRELIMINARY COMPARATIVE EVALUATION ON BIOCHEMICAL PARAMETERS - Tripathy, Ratikanta; Pradhan, Manas Ranjan; Shrivastav, Vartika; Das, Abheek; Jhajharia, Sumit; Mohapatra, Tribhuban M (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: There are limited therapies available for prevention and treatment of hepatitis following antitubercular therapy. Very few reports are available regarding the hepatoprotective activity of Tridax procumbens (Tridax daisy) and Ficus religiosa (Aswatha) against the hepatitis induced by antitubercular drugs. Hence, we studied the hepatoprotective activity of Tridax and Ficus in isoniazid- and rifampicin-induced hepatitis in rats. Methods: The rats were divided into five groups. Group 1 - Control, Group 2 - Toxic control received isoniazid + rifampicin (100 mg/kg intraperitoneal each), Group 3 - Received Tridax extract (200 mg/kg p.o.) along with isoniazid and rifampicin, Group 4 - Received Ficus extract (200 mg/kg p.o.) with isoniazid and rifampicin, Group 5 - Standard group receiving Liv-52 (10 mg/kg p.o.) along with isoniazid and rifampicin. After 21 days, alkaline phosphatase (ALP), alanine transaminase, aspartate transaminase, and bilirubin levels were estimated from the serum. One-way ANOVA was applied to test for significance of biochemical data of the different groups. The significance is set at pâ‰¤0.05. As evident from our study, rats receiving Tridax shows significant improvement in all liver function test (LFT) parameters. Results: There is a significant difference in all the LFT parameters between Tridax group and Liv-52 group (p=0.004 for total bilirubin, 0.001 for ALP). Between Liv-52 group and Ficus group only significant in total bilirubin (p=0.04). Conclusion: From this study, it can be concluded that methanolic extract of both Tridax and Ficus has got significant hepatoprotective effect. Keywords: Isoniazid, Rifampicin, Liver function tests, Hepatoprotective.